2020
DOI: 10.3390/ma13081908
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Non-Destructive Techniques for Technological Bridge Deflection Testing

Abstract: This paper presents a comparison and assessment of usefulness of various measuring techniques (terrestrial laser scanning (TLS), tachymetry, photogrammetry) applied to establish the behavior of a suspension bridge under different load scenarios. The applied techniques were examined on the bridge with a 165 m span. The tested structure works as the technological bridge for a belt conveyor linking a lime mine and cement plant. The testing range consisted of conducting the non-contact measuring of the bridge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Jiang et al [8] concluded that close-range photogrammetry technology is a powerful measurement method that can provide unique solutions for a variety of bridge engineering applications. Kwiatkowski et al [9] compared and evaluated the usefulness of various measurement techniques (terrestrial laser scanning (TLS), tachymetry, photogrammetry) applied to establish the behavior of suspension bridges under various loads. Gawronek et al [10] measures the vertical displacement of railroad bridges using terrestrial laser scanning (TLS) technology, and confirmed that this technology can provide reasonable results for quick assessment of railway infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [8] concluded that close-range photogrammetry technology is a powerful measurement method that can provide unique solutions for a variety of bridge engineering applications. Kwiatkowski et al [9] compared and evaluated the usefulness of various measurement techniques (terrestrial laser scanning (TLS), tachymetry, photogrammetry) applied to establish the behavior of suspension bridges under various loads. Gawronek et al [10] measures the vertical displacement of railroad bridges using terrestrial laser scanning (TLS) technology, and confirmed that this technology can provide reasonable results for quick assessment of railway infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Computer vision, a field that enables computers to recognize and analyze visual information, has been continuously developed [17][18][19][20][21]. Deep learning techniques have recently introduced numerous applications in computer vision [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of laser scanning, a target point and separate data network are not required for data acquisition. The necessary equipment for this procedure is a laser scanning device and a laptop computer, which allows the researcher to obtain data on the entire surface of the structure [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%